QoS-based cloud ERP selection model for SMEs - Ogunrinde, Rowland R.; Jusoh, Yusmadi Yah; Che Pa, Noraini; Wan Ab. Rahman, Wan Nurhayati; Abdullah, Azizol (Penerbit Universiti Teknikal Malaysia Melaka, 2017)
The roles played by Enterprise Resource Planning (ERP) systems in any organizations in achieving operational excellence and competitive advantage cannot be underestimated. However, the cost of implementing traditional ERP has been observed to be a bane for most Small and Medium Enterprises (SMEs) which are globally known as the major drivers of most agile economies. Cloud computing is a paradigm technology concept that affords the SMEs opportunities of affordable services in which ERP can be Cloud-hosted and rented on pay-per-use basis, which does not require a great deal of initial capital to ensure business continuity in a highly competitive market. There are a lot of providers offering ERP as Software-as-a-Service (SaaS), the SMEs therefore is being faced with the challenge of selecting a provider with Quality of Service (QoS) suitable enough to meet the customized requirements of the organizations. A model is presented in this paper which seeks to address this selection challenge. Apart from the suitability efforts, the model also further attempts to select the cheapest among a few selected providers already found suitable for the SMEs.